História do Colégio São Carlos de Caxias do Sul, Rio Grande do Sul (1936-1971) - Paz, Valéria Alves (My University, 2014)
This study had the purpose to research, analyze and understand the St. Carlos College‟s historical process, established by the Sisters‟ Congregation of St. Carlos Borromeo - Scalabrinians in 1936 in Caxias do Sul. Thinking in school cultures that institution, sought to construct a historical narrative contemplated his daily life: subjects, practices, spaces and times lived in St. Carlos College. The study was based on theoretical assumptions of Cultural History. The sources used were written documents (reports, projects, teaching guidelines, school movement, etc.). and produced photos and archived by the institution, as well as documents the João Spadari Adami‟s Municipal Historical Archives So, I tried to interpret in a less homogenizing way the school‟s world, developing a larger view regarding school practices through the enhancement of everyday actions, professionals, its history and gender issues. The text was organized into four chapters: the opening remarks with a brief emphasis on how the research process was, in Chapter 2, the historical context of the decades from 1930 to 1970 of Caxias do Sul, portraying the role of women in the Caxias do Sul society, their education and training of the Congregation Scalabrinian. In chapter 3, I analyzed how this congregation was structured in Caxias do Sul and its educational activities with the creation of the St. Carlos College. Finally, in Chapter 4, I discussed the school practices of the institution in relation to their students, rituals and routines. In the final considerations, I conclude by stating the importance of women's role and their educational process through the Carlist congregation‟s agency. Disseminating a vision of women purity, the Sisters have advocated the girls‟ education providing knowledge through many courses that were offered by the college. Acted educating these girls, considering what the Church craved as ideal for women. Then, the College's work educating the Caxias do Sul‟s women was a great work, but not only that. Telling the history of this institution, it was contributed to thinking about education in Caxias do Sul and in the state of Rio Grande do Sul, the female enrollment, contribution and interfaces between school and church, among other things, in historical perspective.
O presente trabalho teve como propósito pesquisar, analisar e compreender o processo histórico do Colégio São Carlos, criado pela Congregação das Irmãs de São Carlos Borromeo – Scalabrinianas, em 1936, em Caxias do Sul. Pensando nas culturas escolares dessa instituição, busquei construir uma narrativa histórica que contemplou o seu cotidiano: sujeitos, práticas, espaços e tempos vividos no Colégio São Carlos. O estudo baseou-se nos pressupostos teóricos da História Cultural. As fontes utilizadas foram os documentos escritos (relatórios, projetos, orientações didáticas, movimento escolar, etc.) e fotográficos produzidos e arquivados pela instituição, bem como os documentos do Arquivo Histórico Municipal João Spadari Adami. Assim, busquei interpretar de maneira menos homogeneizante o universo da escola, desenvolvendo uma visão mais ampla em relação às práticas escolares através da valorização das ações cotidianas, dos profissionais, de sua trajetória, além de questões de gênero. O texto foi organizado em quatro capítulos: as considerações iniciais com uma breve ênfase de como foi o processo da pesquisa; no capítulo 2, o contexto histórico das décadas de 1930 a 1970, de Caxias do Sul, retratando o papel da mulher na sociedade caxiense, sua educação e a formação da Congregação Scalabriniana. No capítulo 3 analisei de que forma essa congregação se estruturou em Caxias do Sul e suas atividades educacionais com a criação do Colégio São Carlos. Por fim, no capítulo 4, abordei as práticas escolares da instituição em relação aos seus discentes, os rituais e as rotinas. Nas considerações finais, concluo afirmando a importância do papel da mulher e seu processo educativo através da atuação da congregação carlista. Disseminando uma visão de pureza da mulher, as Irmãs preconizaram a educação das moças proporcionando conhecimentos através de vários cursos oferecidos pelo colégio. Atuaram educando essas moças, considerando o que a Igreja almejava como ideal para a mulher. Assim, foi de grande êxito o trabalho do Colégio na educação da mulher caxiense, mas não apenas. Ao narrar a história dessa instituição contribuí para pensar a educação em Caxias do Sul e no Rio Grande do Sul, a escolarização feminina, a contribuição e as interfaces entre escola e Igreja, entre outros aspectos, em perspectiva histórica.
Keywords: Colégio São Carlos - História; Escolas particulares - Caxias do Sul (RS); Escolas católicas; Confessional schools; Religious congregation; Institution‟s History